Soil C and N dynamics and their non-additive responses to litter mixture under different moisture conditions from an alpine steppe soil, Northern Tibet. (October 2018) - Chen, Youchao; Ma, Shuqin; Liu, Jing; Cheng, Genwei; Lu, Xuyang
Abstract: Although there is a strong consensus that biodiversity can influence ecosystem functioning, how litter diversity affects soil ecological processes in different climatic contexts has been rarely studied. Here, we employed a mixed-litters' experiment to examine how mixed-litters decomposition affects soil carbon (C) and nitrogen (N) dynamics under different moisture conditions from an alpine steppe soil in Northern Tibet. Litter of alpine steppe species, in monoculture or combination, were mixed with soil in 20%, 30% and 40% water holding capacities (WHC) in microcosms. During each microcosm incubation, we measured CO2 emissions, soluble organic carbon (SOC), total inorganic N (TIN) and microbial biomass C (MBC). Our results showed that CO2, SOC, TIN and MBC differed significantly among litter treatments and soil moisture. In the litter mixture, frequent and unsystematic non-additive effects could be found in CO2, SOC, TIN and MBC, and the non-additivities could be explained by the litter chemical traits. Higher soil moisture strengthened the synergistic effects of litter-mixing on CO2 and antagonistic effects on TIN, while weaken the synergistic effect on SOC and the antagonistic effects on MBC. This result indicated that, under multiple litter species decomposition, a changing soil moisture from dry to wet generally accelerate CO2 emission and increase MBC, while decrease the accumulation of SOC and TIN. Our work demonstrated that soil C and N dynamics and their non-additive responses to litter mixture were climatic context dependent. Soil moisture condition should be considered in understanding the effects of litter diversity on soil C and N processes. Highlights: Litter mixture has idiosyncratically non-additive effects on soil C and N. Litter-mixing effects on soil C and N were determined by litter chemical traits. Soil moisture conditions alter litter-mixing effects on soil C and N.